Sistem Informasi Kesehatan Balita Pada Posyandu Burung Elang Berbasis Website - Alim, Muhammad Faishal; Purabaya, Rudy Ho (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2024)
At this time with the rapid development of technology, it requires that someone can complete most of the work efficiently by using a computer as an information system and data processing with a fast process. Posyandu Burung Elang RT.002 / RW.02 Ciracas East Jakarta is one of the posyandu that still uses manual data processing through the Maternal and Child Health Reporting book (KIA) and the Towards Healthy Card (KMS) in managing data recording new child data, weighing data, immunization data, calculating the age and nutritional status of children, and reporting between posyandu cadres and the health department. To achieve ease in efficient data processing at Posyandu Burung Elang RT.002 / RW.02, in overcoming this, a website-based information system is needed using the Waterfall method as a design method and PIECES as a method of analyzing work system identification and with UML modeling, which is built using the Laravel framework and MySQL database. The results of this study produce a website-based information system that can manage data, calculate the age and nutritional status of children automatically, whether nutrition is included in the category, make it easier for parents to monitor child development as well as early registration for Posyandu activities and Posyandu cadres are facilitated in recording children and making reports on Posyandu Burung Elang RT.002 / RW.02 Ciracas.